Kerjasama Pemerintah Indonesia-Malaysia Dalam Menangani Peredaran Narkotika di Wilayah Perbatasan - Suzeeta, Nala Syandhira; Prasetyo, Handoyo (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this research is to find out what form of cooperation is carried out by the Indonesian - Malaysian government in an effort to deal with the circulation of narcotics in the border area and to find out what the impact will be if the circulation of narcotics in the border area is not stopped. This research uses a normative juridical method by referring to legal norms contained in statutory regulations as well as legal norms that exist in society. An approach that refers to applicable laws and regulations including principles, principles and doctrine. The cooperation carried out between the Governments of Indonesia and Malaysia is a cooperative international relationship. This collaboration is carried out with the common goal of overcoming drug trafficking. In this effort, Indonesia and Malaysia are also collaborating with non-governmental organizations to deal with drug trafficking and abuse. In eradicating drug trafficking networks and routes from Malaysia, POLRI collaborates with PDRM. This collaboration began with the signing of a Memorandum of Understanding between POLRI and PDRM signed in Bali on 19 May 2005. The threat of abuse and distribution of illegal narcotics has grown rapidly and is very worrying for the global community because the abuse of narcotics has negative impacts that can cause death. This abuse is also very vulnerable to occurring among the younger generation, where the younger generation will later become the nation's successors. In this case, it means that emerging threats can disrupt human life in various sectors, such as politics, economics, socio-culture and health.